Corporate Social Responsibility Disclosure dan Earning Response Coefficient (ERC) Perusahaan Pertambangan Di Indonesia - Teguh Erawati; Elisabeth Lusitania Lota Losor (Jurnal Simki Economic, 2023)
The purpose of this research is to find out whether there is an influence of corporate social responsibility disclosure and Earning Response Coefficient in mining companies listed on the IDX with the research year 2012-2016. The sample selection was carried out using a purposive sampling technique and it was found that fifteen manufacturing companies had an observation period of 5 years, namely 2012-2016, so the total sample obtained was 75 annual reports of mining companies. Based on the results of the research carried out, it can be concluded that the corporate social responsibility disclosure variable does not have a positive influence on ERC, while the earning response coefficient variable have a positive effect on the IDX in 2012-2016.